Interpretasi Foto Udara untuk Identifikasi Ekosistem Pantai dan Pulau-Pulau Kecil - Tahir; Andrias (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2024)
Variations in coastal and small island ecosystems cannot be separated from the condition of sea waters and the influence of activities occurring on land. Continuous processes that occur in the sea and on the land will, of course, influence genetic processes and the materials that make up them, so that coastal and small island ecosystems provide special characteristics and unique internal problems. This research aims to identify coastal ecosystems and small islands in West Muna Regency using aerial photography based on the forming parameters that influence the constituent ecosystems. The method used to identify coastal ecosystems and small islands is through an aerial photo interpretation and field survey approach. The research results show that the condition of the coastal ecosystem and small islands of West Muna Regency is influenced by activities that occur on land and at sea which interact and interact with each other, thus influencing the environmental dynamics of the coastal ecosystem. Therefore, the management of coastal and small island ecosystems in West Muna Regency requires an integrated and comprehensive approach so that coastal and small island ecosystems can be sustainable.